Implementing modified same-day discharge protocol. (2nd July 2022) - Abdelmalak, M; Ibrahim, W; Shawki, S; Omar, O; Omar, O
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: To accomplish overcapacity and bed lacks same-day discharge post percutaneous coronary intervention (PCI) has appeared as a key to improve resource consumption. Also, to focus on evaluating the length of hospital stay (LOS) post PCI's patients and how to decrease the LOS or same day discharge . Aim: A quality improvement project that aimed for implementing new modified Same Day Discharge (SDD) protocol post- Percutaneous Coronary Intervention (PCI) in purpose to decreasing the patient LOS, resources utilization, improving patient satisfactions, manage overcrowded, bed shortages, and bed-flow efficiency. Methods: After modifying the protocol to fit with the new cardiac care setting. Orientation for staff nurses about SDD protocol. Statistical results compared to determine the impact of the new modified SDD protocol regarding the LOS. (Figure B) Patients who fit the criteria will be discharge on the same day post PCI. (Figure C) Results & Data Analysis: During Sep. 2020, the total patients were 196 (PCI 64 Patients ) compared to 165 (PCI 26 Patients) on Sep. 2021. PCI patients who met the SDD criteria and did not discharge were 48% on Sep. 2020 compared to 19% on Sep. 2021. As showing on the data there is significant impact of the SDD modified protocol, there are 29% increased on the patient discharge. Recommendation: Continuous using of these criteria. Link the patient LOS to the data to assess how the SDD Impact and to support the result. Conclusion: SDD protocol for post PCI patient in carefully selected patients that improve the patient discharge process.